2011
DOI: 10.1002/rra.1607
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate Response to Flow Changes in a Subalpine Stream: Predictions From Two‐dimensional Hydrodynamic Models

Abstract: Two-dimensional hydrodynamic models are being used increasingly as alternatives to traditional one-dimensional instream flow methodologies for assessing adequacy of flow and associated faunal habitat. Two-dimensional modelling of habitat has focused primarily on fishes, but fish-based assessments may not model benthic macroinvertebrate habitat effectively. We extend two-dimensional techniques to a macroinvertebrate assemblage in a high-elevation stream in the Sierra Nevada (Dana Fork of the Tuolumne River, Yos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 88 publications
(87 reference statements)
1
14
0
1
Order By: Relevance
“…A 2D numerical hydrodynamic model, River 2D, was used to generate spatial maps of current velocity (V) and water depth (D) over the entire study area. The accuracy of the simulation depended strongly on the quality of bed topography data [49]. In this study, the simulated results showed strong agreement with the empirical data, supporting River 2D's applicability to small scale analysis [12].…”
Section: Usefulness Of River 2d In Simulating Flow Conditionssupporting
confidence: 74%
“…A 2D numerical hydrodynamic model, River 2D, was used to generate spatial maps of current velocity (V) and water depth (D) over the entire study area. The accuracy of the simulation depended strongly on the quality of bed topography data [49]. In this study, the simulated results showed strong agreement with the empirical data, supporting River 2D's applicability to small scale analysis [12].…”
Section: Usefulness Of River 2d In Simulating Flow Conditionssupporting
confidence: 74%
“…Two‐dimensional hydrodynamic models have been used to evaluate aquatic habitat for a variety of fish species (Gard, ; Guay et al, ; Boavida et al, ) and invertebrates (Waddle and Holmquist, ; Alexander et al, ), as well as for planning and assessing river rehabilitation design (Wheaton et al, ; Pasternack et al, ; Brown and Pasternack, ; Gard, ). They are useful tools for describing the spatial distribution of hydraulic variables relevant to aquatic habitats, such as mean column water velocity (velocity), water depth (depth) and bed shear stress within the river channel over varying discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Their habitat preferences were assessed using the “benthos‐GR” dataset (https://github.com/chtheodoro/benthos-GR), consisting of 380 microhabitat observations collected from nine sampling sites in Greece (Theodoropoulos et al, ). Each microhabitat is a combination of V, D, and S corresponding to a habitat suitability value ( κ ), calculated using BM‐community metrics commonly applied to assess the quality–suitability in relevant studies (Englund & Malmqvist, ; Holmquist, Schmidt‐Gengenbach, & Roche, ; Monk et al, ; Waddle & Holmquist, ). Each metric was weighted based on a combination of expert‐judgement and previous literature to reflect its relevant contribution‐significance to the calculation of κ and the following equation was used: italicκ=0.40.25emitalicnitalicijitalicnitalicjmax+0.30.25emitalicHitalicijitalicHitalicjmax+0.20.25emitalicEPTitalicijitalicEPTitalicjmax+0.10.25emitalicaitalicijaitalicjmax where κ is the calculated habitat suitability of the ith microhabitat of the jth site, ranging from 0 to 1. n ij denotes the number of BM taxa (families) found at the ith microhabitat of the jth site. H ij denotes the Shannon's diversity index for the ith microhabitat of the jth site. EPT ij is the number of EPT taxa found at the ith microhabitat of the jth site. a ij is the abundance of benthic macroinvertebrates found at the ith microhabitat of the jth site. n jmax , H jmax , EPT jmax , and a jmax denote the maximum value of the relevant variables observed at the jth site. …”
Section: Methodsmentioning
confidence: 99%
“…A three‐class hierarchy of EFA methodologies has been suggested, with HHMs being considered as “level 3,” potentially applicable in situations where a high degree of certainty is required to provide water managers with defensible eflow recommendations. But despite the excessive long‐term research, the improved predictive accuracy, and the wide recognition of their effectiveness in providing accurate EFAs, the practical application of HHMs in EFAs in Europe remains disproportionately limited compared with their hydrology‐based alternatives (Dunbar, Alfredsen, & Harby, ; Linnansaari, Monk, Baird, & Curry, ; Rivaes, Boavida, Santos, Pinheiro, & Ferreira, ) and is primarily focused on fish (Arthington, ; Leitner, Hauer, & Graf, ; Waddle & Holmquist, ). The low percentage (18%) of European HHMs‐based case studies in the relevant WFD Guidance Document is also indicative of this gap between theoretical research/knowledge and practical application of HHMs.…”
Section: Introductionmentioning
confidence: 99%